Glutathione S Transferase Theta1 and Mu1 (GSTT1 and GSTM1) Deletion Among Autistic Population of India - Hegde, Rajat; Hegde, Smita; Kulkarni, Suyamindra S.; Das, Kusal K.; Gai, Pramod B. (Current Psychiatry Research and Reviews, 2024)
Introduction: Oxidative stress is an imbalance between an organism's reactive oxygen species (ROS) production and antioxidant defence capacity. Long-term oxidative stress contributes to cellular ageing and plays a role in the pathogenesis of several diseases. Several investigations indicated that oxidative stress has a role in the pathogenesis of ASD. Objectives: Present study was undertaken to record the association of GSTTT1 and GSTM1 null genotype among the autistic population of India. Methods: Genomic DNA was isolated from 108 autistic children along with healthy agematched control. The quality and quantity of the isolated genomic DNA were analysed. GSTT1 and GSTM1 null genotype was analysed using polymerase chain reaction with internal positive control. Statistical analysis was performed using SPSS 15.0. Results: Present study included 85 males and 23 females with a mean age of 11.7 ± 3.5 and 75 males and 33 females with a mean age of 11 ± 2.0 in the control group. 32 (29.6%) autistic cases showed null genotypes for GSTT1 and 21(19.4%) autistic children showed null genotypes for GSTM1. 3 (2.85%) control children showed a null genotype for GSTT1 and 5 (4.6%) control children showed a null genotype for GSTM1. The GSTT1 and GSTM1 null genotypes were observed to be significantly associated with the risk of autism (p value-0.0001, OR-14.73, 95% CI 4.35-49.90) and (p value-0.003, OR-4.731, 95% CI 1.71-13.08) respectively. Conclusion: The findings of our study suggested that GSTT1 and GSTM1 null genotype is one of the potential risk factors for autism through oxidative stress mechanism in our population.
Keywords: Oxidative stress